Perlindungan Hak Kekayaan Intelektual Dalam Hukum Persaingan Usaha: Perspektif Komisi Pengawas Persaingan Usaha - Wijayanto, Budi Tri; Sumanto, Listyowati (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Intellectual Property Rights are exclusive rights the state grants to inventors or creators of their intellectual works. Competition Law and the role of the Business Competition Supervisory Commission are closely related in ensuring the protection of intellectual property rights in Indonesia to prevent a decline in competitiveness and investment climate, including potential activities that can harm consumers such as the circulation of counterfeit products, price instability, and maintaining Indonesia's image in the international arena. This paper aims to provide an overview of the Business Competition Supervisory Commission's important role in ensuring the protection of intellectual property rights within the framework of healthy business competition law in Indonesia. The research method used is a descriptive normative legal research type. The data collection technique used is a literature study. Secondary data is analyzed qualitatively, and conclusions are drawn using deductive logic. The results of the study show that regulations give the Business Competition Supervisory Commission the authority to take action against business actors who violate intellectual property rights, monopolistic practices, and unfair business competition, such as unfair pricing, production restrictions, and exclusive agreements. Thus, the Business Competition Supervisory Commission has an important role in ensuring the protection of intellectual property rights to create a healthy business competition climate.